Plasma ghrelin levels in various stages of development of iron deficiency anemia - Akarsu, Saadet; Ustundag, Bilal; Gurgoze, Metin K.; Sen, Yasar; Aygun, Abdullah D. (Lippincott Williams & Wilkins, 2007)
Objectives: Ghrelin stimulates food intake and induces metabolic changes leading to an increase in body weight and body fat mass. Iron-deficiency anemia (IDA) is the most frequently seen cause of nutritional anemia, that is a type of starvation. There is no available study related to levels of ghrelin in IDA. The aim of this study is to show an association with ghrelin levels and iron deficiency and to demonstrate whether changes seen in iron deficiency (ID) are explained by ghrelin, as opposed to whether ghrelin levels correlate with ID. Materials and Methods: The study group was consisted of children who were admitted in the outpatient clinic of pediatrics. Control group (C) was defined as cases with normal hemoglobin (Hb), serum iron (SI), transferrin saturation (TS), and ferritin (F) (>12 ng/mL) values; group hypoferritinemia (IDec) Hb: N, SI: N, TS: N, F < 12 ng/mL; group iron deficiency (IDef), Hb: N, SI: decreased, TS <= 16%, F < 12 ng/mL, and group IDA, Hb and SI decreased, TS :! 16%, F < 12 ng/mL. The patients were categorized into 4 groups [group I (C), n = 25, age = 82.4 +/- 16.56 mo, F 40.87 +/- 6.17 ng/mL; group 2 (IDec), n = 30, age = 57.5 +/- 20.71 mo, F = 29.95 +/- 3.77 ng/mL; group 3 (IDef), n = 28, age 50.21 +/- 19.87 mo, F 14.82 +/- 3.41 ng/mL; group 4 (IDA), n 25, age = 31.55 +/- 13.21 mo, F = 11.75 +/- 4.01 ng/mL]. Results: Mean value of ghrelin was detected to be 396.53 +/- 85.56 pg/mL, 332.26 +/- 74.35 pg/mL, 309.66 +/- 68.62 pg/mL, and 177.66 +/- 27.81 pg/mL in control, groups IDec, IDef, and IDA, respectively. A statistically significant difference was detected between groups control and IDef (P < 0.01), control and IDA, IDec and IDA, IDef and IDA (P < 0.001). Conclusions: A significant positive correlation was demonstrated between iron status of the body and levels of ghrelin. Decrease in ghrelin levels in IDA can lead to loss of appetite, desire to eat diverse foods with resultant delay in growth and development.
Keywords: ghrelin; iron deficiency anemia; child